Tensile Strength of Brittle Materials in High Strain Rate Processes - Mianowski, K.M. (Engineering Transactions, 1988)
Assuming that high strain rate tensile tests lead to brittle fracture (no slip mechanisms participate in the process), the phenomenon of strength growth in very fast processes is attributed to thermal vibrations of crystal lattice. Formulae are given enabling effective evaluation of strength as a function of duration of the loading process. Results of analysis are compared with experimental data published by Zieliński and concerning the tensile strength of concrete in high rate processes.